ÖZEL ÖĞRENME GÜÇLÜĞÜNDE YAZILI ANLATIM VE YAZMA KAYGISI. - ÖZTÜRK, Halil; GİRLİ, Alev (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2017)
Written expression is a skill that is frequently used by the individual in the school process and daily life and is necessary for these areas. In daily life, individual can convey ideas, thoughts, opinions or feelings in written form. Expressing oneself in writing is not only a difficult process for individuals with learning disabilities but also a problem that many learners experience, unaffected by the power of learning. It is an anxious process due to the features contained within the writing process. The high level of writing anxiety can cause students to avoid writing skills by influencing their success in writing. This study compared the level of written expression and writing anxiety of middle school students (5th, 6th and 7th grade) with special learning disabilities and their peers with normal development. As a result of the study, it was found that the students with special learning difficulties had a higher level of writing anxiety compared to medium and high level of writing anxieties, the ones with normal development, and there was no meaningful relation between writing anxiety levels and written expressions.